2020
DOI: 10.3390/ijms21186963
|View full text |Cite
|
Sign up to set email alerts
|

Sudachinoid- and Ichangensin-Type Limonoids from Citrus junos Downregulate Pro-Inflammatory Cytokines

Abstract: Limonoids, a dominant group of phytochemicals in the Rutaceae family, are known to exhibit several pharmacological activities. To identify natural products having efficacy against inflammatory bowel disease (IBD), we isolated 13 limonoids including a new compound, methyl sudachinoid A, from the seeds of Citrus junos and investigated their anti-inflammatory effects by assessing the expression of pro-inflammatory cytokines in lipopolysaccharide-stimulated RAW 264.7 mouse macrophages and HT-29 human colon epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The expression levels of inflammatory factors such as TNF-α, IL-1β, and IL-6 in UC were increased by abnormal activation of the PI3K/AKT signalling pathway (Li et al 2019a , b ; Li et al 2019a , b ). Furthermore, TNF-α is an important proinflammatory cytokine involved in the pathogenesis of UC, inducing the pathological opening of the intestinal tight junction barrier, increasing intestinal epithelial permeability, and disrupting intestinal barrier function (Xiang et al 2021 ; Shin et al 2020 ). Therefore, anti-TNF-α therapy has been widely used in clinical practice as a suitable method of UC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of inflammatory factors such as TNF-α, IL-1β, and IL-6 in UC were increased by abnormal activation of the PI3K/AKT signalling pathway (Li et al 2019a , b ; Li et al 2019a , b ). Furthermore, TNF-α is an important proinflammatory cytokine involved in the pathogenesis of UC, inducing the pathological opening of the intestinal tight junction barrier, increasing intestinal epithelial permeability, and disrupting intestinal barrier function (Xiang et al 2021 ; Shin et al 2020 ). Therefore, anti-TNF-α therapy has been widely used in clinical practice as a suitable method of UC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…About 13 limonoids were isolated from Citrus junos (Shin et al, 2020) Gendunin-A (284) and nimbolide (287), both isolated from Azadirachta indica, displayed antiinflammatory activity (Braga et al, 2020). In the case of compound 287, a clinical therapeutic value in rheumatoid arthritis by inhibiting the STAT-3/NF-κB/Notch-1 axis and reducing the levels of proinflammatory cytokines was also observed (Anchi et al, 2021).…”
Section: Saponins-compounds 205-247mentioning
confidence: 99%
“…About 13 limonoids were isolated from Citrus junos (Shin et al, 2020) being 10 of them ( 274–283 ) acting as suppressors of the expression of IL‐8 stimulated by LPS at concentrations of 1 and 10 μM. Sudachinoid‐type limonoids methyl sudachinoid A ( 274 ) and sudachinoid B ( 275 ) reduced the pro‐inflammatory cytokines in LPS‐stimulated macrophages at both tested concentrations.…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
“…Limonin exhibits several significant biological and pharmaceutical activities, including antioxidant, antibacterial, antitumor, analgesic, and anti-inflammatory effects [ 21 , 22 ]. Limonin has been reported to suppress the NF- κ B pathway in RAW 264.7 macrophages stimulated by LPS [ 23 ]. Meanwhile, it has also been shown that limonin may activate Nrf2 in HepG2 cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%